New Florida Foliage Plant Cultivar: Aglaonema 'Moonlight Bay' - Richard J. Henny; Jianjun Chen; Terri A. Mellich (EDIS)
ENH1167, a 4-page illustrated fact sheet by R.J. Henny, J. Chen, and T.A. Mellich, describes Aglaonema Moonlight Bay, a new ornamental foliage plant that is a result of a mutation discovered in the Aglaonema Silver Bay plant – description, availability, and origin. Includes additional sources of information. Published by the UF Department of Environmental Horticulture, July 2010.